(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2009)
This article investigates the hermeneutical problem of how the Bible should be read and understood. It deals with the older historical critical method (still in use), the different literary-critical methods developed afterwards, as well as the latest so-called “new hermeneutics” with a clear philosophical bias. The question is whether these methods can be of use to interpret the Bible in such a way that God speaks. And if it are not capable to do so, is there another way out? The investigation develops through the following steps: (1) The positive and negative sides of the historical-critical and literary-critical methods are investigated. (2) This is followed by a brief exposition of the “hermeneutical revolution”, starting about the 60’s of the previous century. (3) This most recent development in hermeneutics necessitates a clarification of the relationship between worldview and the interpretation of the Bible. (4) In the light of the fact that theological hermeneutical methods often obstruct the access of “ordinary” believers to God’s Word, the wrong as well as correct relationships between pre-scientific faith and scientific theology are discussed. (5) The next step is to argue in favour of a direct, theologically unmediated access to the Scriptures of “ordinary” Bible readers. (6) The final part provides an example of this pre-scientific access in showing how the metaphors of salt and light clearly indicate a Christian’s calling to beinvolved in social issues.